A survey study on integration of warehouses and distribution centres - Lee, Felicia Ching Yee. (2011)
This project is aimed at finding out the advantages and disadvantages of integration, whether warehouses and distribution centres have carried out integration to synergise their business, whether integration brings about more benefits to the companies as well as the reasons that are preventing companies from carrying out integration. In addition, this project also aims to gather the perspectives of the warehouses and distribution centres industry regarding integration.